PENDEKATAN PEMBELAJARAN BERDIFERENSIASI DI SD UNTUK MENYESUAIKAN KEBUTUHAN SISWA YANG BERAGAM - Nur Denisa (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2026)
The differentiated learning approach is a strategy that adapts teaching to students' diverse needs, abilities, interests, and learning styles. In elementary schools, this approach is essential to ensure that all students can learn optimally according to their characteristics. This study aims to describe the implementation of differentiated learning and its impact on student engagement and learning outcomes. The method used is a literature study with a qualitative descriptive approach. The results show that the application of differentiated content, process, and product can improve student participation, motivation, and overall learning achievement.